EVALUASI PENGGUNAAN OBAT ANTI TUBERKULOSIS PADA PASIEN ANAK DI INSTALASI RAWAT JALAN RSUD BALARAJA KABUPATEN TANGERANG PERIODE JANUARI – DESEMBER 2020 - Sri Komalasari; Siva Fauziah; Nurfitriyana (Institut Sains dan Teknologi Al-Kamal, 2025)
Tuberculosis (TB) is a highly contagious infectious disease caused by the bacterium Mycobacterium tuberculosis. Indonesia is one of the countries with the highest number of tuberculosis sufferers in the world. With the increasing incidence of TB in adults, the number of children infected with TB will increase and the number of children with TB disease will also increase. It is difficult to diagnose TB in children, causing over-diagnosis and over-treatment in the treatment of TB in children. This study aims to determine the characteristics of tuberculosis patients and determine the accuracy of tuberculosis drug treatment for children including the right diagnosis, the right drug, the right dose and the duration of treatment. This research is a type of non-experimental research with a descriptive research design by taking data from medical records retrospectively. The sampling technique used is purposive sampling . The total sample obtained was 52 patients who had met the inclusion and exclusion criteria. The data obtained were then compared for compliance with the 2016 National Guideline for Tuberculosis Management. The results of the analysis of 52 samples showed that the suitability of pediatric lung treatment in the outpatient installation of Balaraja Hospital, Tangerang Regency based on the accuracy of diagnosis as many as 52 patients (100%), accuracy In the intensive phase there were 52 patients (100%) while in the follow-up phase there were 50 patients (100%), the accuracy of the dose was 84.62% and the overall frequency of treatment of OAT in patients showed 100% therapeutic accuracy. The use of anti – tuberculosis drugs for children include the right diagnosis, right drug, right dose, and frequency of treatments of OAT is in conformity with Pedoman Nasional Penanggulangan Tuberkulosis.